Evaluation of membrane bioreactor (MBR) technology for industrial wastewater treatment and its application in developing countries: A review - Hemen Emmanuel Jijingi; Sara Kazemi Yazdi; Yousif Abdalla Abakar; Emma Etim (Case Studies in Chemical and Environmental Engineering)
Wastewater treatment has become widely recognized as a highly efficient approach for tackling the pressing issue of limited access to clean water, which is anticipated to give rise to a global crisis in the foreseeable future. This highlights the need to pay close attention to Membrane Bioreactor (MBR) technology, which has emerged as a promising solution for industrial wastewater treatment because of its efficiency and exceptional capability to provide high-quality treated water, especially in developing countries. As industrialization accelerates in these regions, the management and treatment of industrial wastewater present pressing environmental and public health challenges. MBR technology, a combination of membrane filtration and biological treatment, offers a viable solution with distinct advantages, such as enhanced treatment efficiency, smaller footprint, reduced chemical usage, and water reuse potential. This review comprehensively examines MBR technology as a novel and transformative approach to industrial wastewater treatment in developing countries. Some key findings suggest that addressing the challenge of membrane fouling by employing strategies such as selecting appropriate membranes based on specific wastewater characteristics and implementing membrane backwashing and chemical cleaning can extend membrane life and improve performance. The operational success of the Membrane Reactor Technology rests on continuous optimization and control of parameters like Mixed Liquor Suspended Solids (MLSS) concentration and aeration rates, which can maximize treatment efficiency and minimize energy usage. The provision of training for skilled operation and routine maintenance is crucial. The study indicates that successful country-level technology implementation depends on understanding the specific characteristics of local wastewater hydraulic conditions and implementing appropriate pretreatment processes to avoid clogging. Stakeholder collaboration and knowledge sharing are essential for overcoming costs, technical expertise, energy consumption, and regulatory compliance barriers. Further, efforts from governments, industries, and international organizations are necessary to effectively deploy MBR technology, thereby minimizing the environmental impact of industrialization and supporting sustainable development in developing countries.